Energy harvesting using integrated piezoelectric transducer in a composite smart structure for self-powered sensor applications. (April 2023) - Yan, Linjuan; Rodriguez, Jonathan; Billon, Kevin; Lallart, Mickaël; Collet, Manuel; Jean-Mistral, Claire; Chesné, Simon
Self-sensing structures are tremendously needed in transport or energy applications. Nevertheless, structures are rarely designed in advance to harvest energy in realistic operational conditions, leading to sensing functions using most of the time batteries. Thus, this paper proposes a complete application of self-powered sensing using an integrated piezoelectric transducer on a representative composite structure, namely a smart composite reduced-model car. Based on an optimized self-powered Synchronized Switch Harvesting on Inductor circuit (SSHI) coupled with a complete electromechanical behavior study, up to 40μ W can be harvested on a resistive load of 3 M Ω for a linear velocity of 12.5 km.h −1 . This power allows supplying a temperature sensor and its wireless transmitter, whose data can be sent each 60s. Our functionalized car is a first step toward real industrial application cases and demonstrates the ability of the proposed method to enhance the energy harvesting process on an existing weakly coupled structure and use the vibrations as an energy source for relevant embedded microgenerators and associated self-powered sensors.